Nowotny–Juza NaZnX (X = P, As and Sb) as photovoltaic materials. (May 2015) - Reshak, A.H.
Highlights: Calculation show that NaZnSb is a direct band gap semiconductor of about 0.25 eV. Deep insight into the electronic structure can be obtain from optical properties. The uniaxial anisotropy and birefringence confirm the existence of anisotropy. Strong hybridizations exists between Na-s/p, As-d, Zn-s/p, P-p, Sb-p/d states. Abstract: The electronic band structures of Nowotny–Juza NaZnX (X = P, As and Sb) compounds suggest that the valence band maximum (VBM) and the conduction band minimum (CBM) are located at the center of the Brillouin zone, resulting in a direct band gap of about 1.80, 1.47 and 0.25 eV, respectively. The total and the partial density of states explore the type of orbitals which rule the band gaps and to classify the hybridizations between the orbitals. The VBM is formed mainly by P-p, As-p, Sb-p, Zn-p and Na-p states with substituting P → As → Sb. The CBM of NaZnP is formed by Zn-s, Na-s/p, while the CBM of NaZnAs (NaZnSb) is formed by Zn-s and As-d (Zn-s and Sb-d), one can see that As-d and Sb-d orbitals govern the CBM of NaZnAs and NaZnSb, hence these orbitals rule the energy gaps. It is clear that there exists a strong hybridizations between Na-s/p and As-d states, Zn-s/p and P-p states, Sb-p and Zn-s states and also between Sb-d and Na-s states. The strong hybridization may led to form a strong covalent bonding between these atoms. For more detail and to get deep insight into the electronic structures, the optical properties were investigated. The uniaxial anisotropy and the birefringence values confirm the existence of the considerable anisotropy between the two components of the optical properties. The calculation confirm that these compounds are promising candidates for optoelectronics devices.